Pengaruh Metode Talaqqi, Tafahhum, Tikrar dan Muraja’ah (3T+1M) Terhadap Hafalan Al-Qur’an Santri di Ma’had Darut Tahfiz Al-Ikhlas - Risma Dewi, Anggia; M. Duskri; Syahabuddin, Khairiah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
This research aims to determine and analyze the application of tahfiz learning using the talaqqi, tafahhum, tikrar, and murja’ah (3T+1M) methods in learning the Qur’an., and to determine the effectiveness of these methods on students memorization and to find out and analyze the influence of the methode on students motivation in memorizing the Al-Qur’an. this research uses descriptive qualitative research methodes. .Data collection through observation, interviews, memorization tests and distributing questionnaires. The research result show that the application of tahfiz learning using the 3T+1M method is implemented well. The effectiveness of the 3T+1M method for memorizing the Al-Qur’an is categorized as very good with average scores of memorization tests and distributing questionnaires. The research result show that the application of tahfiz learning using the 3T+1M method is implemented well. The effectiveness of the 3 T+1m method for memerizing the Al-Qur’an is categorized as very good with average scores of 88, 92, and 84. Above the KKM tahfiz score limit, namely 80. The influence of the talaqqi, tafahhum, tikrar, and muraja’ah (3T+1M) on the motivation of students in memorizing the Al-Qur’an in Daarut Tahfiz Al-Ikhlas has been very good in persevering in memorizing the Al-Qur’an and is tenacious in repeating his memorization and has high willingness to memorize the Qur’an.